The Role of Online Training Effectiveness on ASN Competency through Learning Motivation: (Study: CPNS Latsar Participants in 2025 in Kaltara Province) - Emilia Pratiwi; Erick Karunia; Shalahuddin Shalahuddin; Mappa Panglima Banding (Jurnal Economic Resource, 2026)
Digital transformation in civil servant competency development requires a comprehensive evaluation of the effectiveness of online training, particularly in archipelagic contexts with limited infrastructure. This research analyzes the influence of online training effectiveness on civil servants' competence, with learning motivation as a mediating variable, among 150 Basic Training participants for prospective civil servants in 2025 in North Kalimantan Province. A quantitative approach employing Structural Equation Modeling with the Partial Least Squares technique was used to examine causal relationships among variables. Results demonstrate that the effectiveness of online training significantly influences learning motivation (β=0.832; R²=0.692) and civil servant competence (β=0.186; R²=0.612). Learning motivation functions as a partial mediator, with an indirect effect of 0.516 that exceeds the direct effect. Total influence reaches 0.702, confirming that high-quality online learning systems, when accompanied by effective motivation cultivation, can substantially enhance civil servants' competence. Findings emphasize the need for an integrative approach to Basic Training program design that combines platform pedagogical quality with comprehensive motivational strategies to optimize competency achievement in the era of governmental digitalization.